Identifikasi Keanekaragaman Jenis dan Pemanfaatan Bambu di Desa Limag Raya Kecamatan Raya. Kabupaten Simalungun - Tri Astuti; Meylida Nurachamnia; Wahyudi Wahyudi (Program Studi Kehutanan, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
Bamboo plants belong to the Gramineae family (grasses). Bamboo has a vital role in people's ecological, economic, and socio-cultural aspects. The high role of bamboo in people's lives is significant, especially in the Simalungun Regency area, to know the types of bamboo that people use. This research aims to determine the diversity of bamboo types and their uses in Limag Raya village, Raya District, Simalungun Regency. The research was conducted in February-March 2023 in Limag Raya Village, Raya District, Simalungun Regency, North Sumatra Province. The object of this research is bamboo plants ( Bambusa sp.) found during field activities. The materials used in the research consisted of tally sheets and questionnaires, plots measuring 25m x 25m, and Results observed in the field. There are seven types, namely: ampel bamboo (Bambusa vulgaris), butar bamboo (Gigantochloa sp), lemang bamboo (Schizostachyum brachycladum), rope bamboo (Gigantochloa apus), oil bamboo, betung bamboo (Dendrocalamus asper), and Sonduk bamboo or ater bamboo (Gigantochloa atter), the INP of the ampel bamboo type has an INP of 65.61%, Lemang bamboo INP of 49.24%, Butar bamboo INP of 26.95%, Sonduk bamboo INP of 16.84% oil bamboo type INP is 12.66%, Betung bamboo has an INP value of 12.60%, and Tali bamboo ( Gigantochloa atter ) has an INP value of 16.10%. Local people use bamboo for handicrafts, such as making baskets (agricultural harvesting containers), coffee-drying places, tampahs, fences, household utensils, building construction (huts), and traditional musical instruments (suling).